Effectiveness Of Article 42 Sentence (1) Uu No. 6 Of 2023 On The Creation Of Work Regarding The Implementation Of The Basis Of Legal Certainty In The Mortgage Agreement By The Banks With The Act Of Binding Agreement Of Sale And Purchase - Faisal Muhammad, Faisal Muhammad; Djumikasih, Djumikasih; Widhiawati, Diah (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
PT Bank Tabungan Negara (Persero) Tbk (Bank BTN) is a State-Owned Enterprise (BUMN) which operates in the banking sector, committed to being a bank that serves and supports housing sector financing. The mission carried out by Bank BTN is to actively support the government in advancing the welfare of the Indonesian people through home ownership and realizing the life that millions of Indonesians dream of through providing decent homes. One type of credit that is still in demand and needed by the public is KPR (Home Ownership Credit). Bank BTN as a bank that focuses on housing financing certainly fully supports the One Million Houses Program launched by the government. It is proven that currently Bank BTN is a bank with market share The largest Home Ownership Credit (KPR) in Indonesia. In order to improve and optimize services to the community with the development of the KPR business and support Bank operations both in terms of business processes and maintaining document quality, there are conditions where it is not possible to make a Sale and Purchase Deed (AJB) so that a temporary binding agreement is needed, namely a Sale and Purchase Agreement ( PPJB). This research aims to determine the implementation of KPR agreements by Bank BTN with sale and purchase binding deeds (PPJB) according to Article 42 paragraph (1) of Law no. 6 of 2023 concerning Job Creation at Bank BTN Kediri. This type of research is empirical juridical legal research and the specifications in this research are descriptive. The source and type of data in this research is primary data obtained from field studies in the form of interviews with Bank BTN Kediri employees. And secondary data was obtained from literature studies related to the theory of legal certainty. The results of this research are that the implementation of the KPR agreement by Bank BTN with the PPJB deed based on Article 42 paragraph (1) of the Job Creation Law does not fully meet the requirements stipulated in Article 42 paragraph (2) of the Job Creation Law.